Pemberdayaan Masyarakat dengan Pengembangan Kearifan Lokal melalui Kerukunan Antar Umat Beragama - Yusuf Hadijaya; Wahyudin Wahyudin; Vivi Wulandari; Siti Kholizah; Vina Amanda; Bunga Artha Nefia Efendi (BADAN PENERBIT STIEPARI PRESS, 2025)
Community Service Program (Kuliah Kerja Nyata/KKN) is a concrete form of the implementation of the Tri Dharma of Higher Education, particularly in the aspect of community engagement. The KKN program in Ndeskati Village, Naman Teran Subdistrict, Karo Regency, 2025, was carried out to optimize the potential of the village while addressing various challenges faced by the community. Ndeskati Village has great potential in horticultural agriculture, yet it still encounters obstacles such as limited use of technology, low environmental awareness, and lack of educational and literacy facilities. Through a descriptive qualitative approach, students conducted observations, interviews, and documentation of several work programs, including strengthening religious moderation, the Smart Children Festival, perwiritan (Islamic gathering), the establishment of a mini garden and family medicinal plants (TOGA), as well as community service (gotong royong). The results showed an increase in community participation in socio-religious activities, the strengthening of solidarity values, improved environmental awareness, and support for children’s educational development. The presence of KKN students not only provided direct contributions to the community but also served as a social learning platform for students to enhance communication, leadership, and teamwork skills. Therefore, the KKN program in Ndeskati Village plays a strategic role in bridging the academic sphere with community life and supporting sustainable village development.